Using Round Robin Technique to Improve Reading Comprehension - Dahlina, Ulinuha; A'i Wahyuni (JEDLISH : Journal Of Education and English Language Teaching, 2021)
The objective of this action research is to improve reading comprehension of Grade XC students of SMA 1 Waringinkurung in the academic year of 2020/2021 through the use of round robin technique. This research was conducted in two cycles with two meetings in each cycle. The steps of this research were planning, conducting action and observation, and having reflection. The participants of the research were the English teacher as the collaborator and the students of class XC. The data of this research were in the form of qualitative and quantitative. The qualitative data were obtained by doing observation as well as interviewing the students and the English teacher. The results of the qualitative data were in the form of field notes and interview transcripts.. Furthermore, to get the trustworthiness of the data, three triangulation principles were implemented: time triangulation, space triangulation, and investigator triangulation. Meanwhile, the quantitative data were obtained from the students’ reading scores of pre-test and post-test. The quantitative data were analyzed by using t-test statistics in SPSS program. The actions implemented in this research were implementing the round robin technique in the reading class, employing the stages of the reading comprehension practice: pre- reading, whilst-reading and post-reading in teaching learning process, and providing input texts which were related to their competencies. The results of the research showed that round robin technique was effective to improve the students’ reading comprehension and students’ participation in reading class. The students’ understanding toward descriptive texts improved. The mean value of the pre-test is 71.61 while the mean value of the post-test is 81.22. The gain score is 9.61. Based on t-test analysis, t value= -9.789; sig. = 0.000, it means that the score difference is significant. In addition, the participations among the students and between the students and the teacher improved. They also became more motivated in learning reading which made them actively engaged in the teaching learning process.